Cybersecurity in higher education: a bibliometric review - Orosco-Fabian, Jhon Richard (2024)
Introduction: ICTs have impacted all sectors of society, especially in higher education, where students are trained to enter the labor market, but will be mediated by these technologies and at the same time exposed to cybersecurity issues. Objective: The aim of the study was to analyze the scientific production on cybersecurity in higher education using bibliometric methods. Method: Bibliometrics was used in the study. The research design was non-experimental of longitudinal type in the quantitative route and interpretative hermeneutic in the qualitative route. Datawrapper, VOSviewer and Bibliometrix were used for data analysis and presentation. Results: The results reveal that cybersecurity in higher education is a growing field since 2003, with exponential growth since 2018, led by authors from Finland, Saudi Arabia and the United States, in specialized journals such as IEEE Security and Privacy. Discussion: scientific mapping identified cybersecurity, cyber threats, cybersecurity awareness, cybersecurity breach, information security and General Data Protection Regulation (GDPR) as central topics, revealing emphasis on studying cybersecurity education. A fertile field of study regarding cybersecurity in higher education is evident.